LO74: Exploring emergency physicians' ability to predict patient admission and decrease consultation to admission time. (May 2019) - Lee, E.; Kwok, E.; Vaillancourt, C.
Abstract : Introduction : Delay of hospital admission until completion of assessment by consultants is a major contributor to emergency department (ED) crowding. We measured emergency physicians' (EP) ability to predict patient admission, and estimated potential time saved if EPs could request a bed at the time of consultation.Methods : This is a prospective cohort study in a tertiary care center over 4 months using a convenience sample of ED patients requiring consultation. We consecutively recruited patients from purposefully selected shifts to balance day of the week and time of day. We excluded patients younger than 18 years or those likely to be admitted (traumas, strokes, STEMI codes, and CTAS1). We asked EPs to predict patient disposition (admission or alternate disposition) just before consultation. We defined admission as: admission to any service, admission within 48 hours of ED discharge, patients held overnight without bed request, or if bed request was delayed by 12 or more hours, and alternate disposition as any other disposition. We present EP prediction test characteristics using sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) with 95% confidence intervals (CI). The potential time saved was calculated from consultation to bed request for admitted patients.Results : Characteristics for the 454 included patients were: mean age 60.1 years, 48.4% male, 46.9% evening presentation, 69.4% were admitted (most commonly by Internal Medicine 26.9%), and median consult to bed request time was 3.5 hours (interquartile range 2.0 – 5.3 hours). Overall EP prediction sensitivity, specificity, PPV and NPV were 90.5% (95%CI 86.7-93.5), 84.2% (95%CI 77.0-89.8), 92.8% (95%CI 89.8-95.0) and 79.6% (95%CI 73.4-84.7) respectively. In other words, EPs correctly predicted 92.8% of patient admissions. The PPV for Internal Medicine was 95.7% (95%CI 89.7-98.4) and ranged from 78.9% (95%CI 53.9-93.0) for Psychiatry to 100% (95%CI 78.1-100) for Family Medicine. A total of 1113.5 hours of ED stretcher time (37.1 hours per shift) could have been saved if EPs initiated a concurrent bed request at time of consultation.Conclusion : EPs correctly predicted 92.8% of patient admissions across a broad field of disciplines. We estimate 1113.5 hours of ED stretcher time could have been saved over the study period if EPs triggered an inpatient bed request at the time of consultation, rather than waiting for the consultants' disposition decision.